Lexical Speech Features of Spontaneous Speech in Older Persons With and Without Cognitive Impairment: Reliability Analysis - Phillip Hamrick; Victoria Sanborn; Rachel Ostrand; John Gunstad (JMIR Aging, 2023)
Abstract BackgroundSpeech analysis data are promising digital biomarkers for the early detection of Alzheimer disease. However, despite its importance, very few studies in this area have examined whether older adults produce spontaneous speech with characteristics that are sufficiently consistent to be used as proxy markers of cognitive status. ObjectiveThis preliminary study seeks to investigate consistency across lexical characteristics of speech in older adults with and without cognitive impairment. MethodsA total of 39 older adults from a larger, ongoing study (age: mean 81.1, SD 5.9 years) were included. Participants completed neuropsychological testing and both picture description tasks and expository tasks to elicit speech. Participants with T-scores of ≤40 on ≥2 cognitive tests were categorized as having mild cognitive impairment (MCI). Speech features were computed automatically by using Python and the Natural Language Toolkit. ResultsReliability indices based on mean correlations for picture description tasks and expository tasks were similar in persons with and without MCI (with r ConclusionsOur findings suggest that automatically calculated lexical properties of speech are consistent in older adults with varying levels of cognitive impairment. These findings encourage further investigation of the utility of speech analysis and other digital biomarkers for monitoring cognitive status over time.